(untitled) (Palimpsesto, 2019)
This article aims at valuing the legacy of De Saussure in the field of foreign language learning and teaching. To avoid digressions, we address only three main issues: the status of Applied Linguistics in the teaching of English, the writing systems in Japanese, and the teaching of Portuguese to Spanish speakers. To contextualize these issues, we describe the socio historical background of the Course in General Linguistics and analyze the dichotomies diachronic/synchronic, signified/signifying, and langue/parole from the perspective of recent semiogenetic and socio semiotic models. The conclusion is that Saussure’s theory proves to be insufficient and restrictive for language learning and teaching, despite the fact that his concept of language underpins both some teaching methods that separate orality from writing and comparative linguistics.